Log-Rank Test as A Continuation of The Kaplan-Meier Method in Survival Analysis Using R Language (Case Study: D-penicillamine Treatment on the Probabillity of Survival in Primary Biliary Cirrhosis (PBC) Patients at the Mayo Clinic) (Jurnal Matematika, Statistika dan Komputasi, 2024)
From 1974 to 1984, Mayo Clinic conducted a D-penicillamine trial to improve the chances of survival of PBC patients. Mayo Clinic conducted a randomized placebo-controlled trial on patients to compare D-penicillamine with D-penicillamine. Mayo Clinic considered other variables besides the time of death or censored time in its study, namely the variables of Ascites, Hepatomegaly, Spider or the presence of esophageal varices, and other PBC symptom variables. Therefore, the author conducted this study to find out D-penicillamine as a drug treatment for PBC by only looking at the variable of time of death or censored time and the variable of drug treatment received by patients during the ten-year data collection period and completing the study with statistical science. Based on that, the author used survival analysis with the Kaplan-Meier and Log-Rank methods to find D-penicillamine as a PBC drug treatment. This study shows how to complete the analysis using the R language. The study results showed that D-penicillamine treatment was not good enough to increase the survival chances of PBC patients
Keywords: Kaplan-Meier; D-penicillamine; Log-Rank Test; Cirrhosis